A brain atlas of astrocyte transcriptomics unveils complex states and responses to Alzheimer's disease neuropathology. (20th December 2022) - Serrano‐Pozo, Alberto; Li, Zhaozhi; Woodbury, Maya E.; Wachter, Astrid; Bryant, Annie G; Noori, Ayush; Welikovitch, Lindsay A.; Jackson, Rosemary J; Lin, Gen; Kwon, Taekyung; Bennett, Rachel E; Talanian, Robert V.; et al.
Abstract: Background: Amyloid‐β plaques and neurofibrillary tangles in the Alzheimer's disease (AD) brain are accompanied by prominent morphological and functional changes in astrocytes, collectively termed reactive astrogliosis. Single‐nuclei RNA‐sequencing (snRNA‐seq) has begun to unveil the molecular underpinnings of AD reactive astrocytes but technical challenges, including low numbers of nuclei and/or sequencing depth, and the lack of comparisons across brain regions have limited the full picture. Here we present the largest snRNA‐seq study of astrocytes to date across five brain regions. Method: Nuclei were isolated from five brain areas of n = 32 donors with increasing AD neuropathology (total n = 160 samples). The five brain areas were chosen based on their hierarchical accumulation of tau pathology: entorhinal cortex (EC)> inferior temporal gyrus (BA20) > dorsolateral prefrontal cortex (BA46) > secondary visual cortex (V2 or BA18/19) > primary visual cortex (V1 or BA17). To enrich in astrocytic nuclei, NEUN+ and OLIG2+ nuclei were separated via FACS, whereas NEUN‐/OLIG2‐ nuclei (including astrocytes) were subjected to snRNA‐seq resulting in a transcriptomic dataset of 629, 755 astrocyte nuclei, which were subsequently examined for common and region‐specific AD related changes. Result: Clustering within each brain region identified likely homeostatic and reactive subclusters, as well as six other clusters which we describe as "intermediate" subclusters. Homeostatic and reactive astrocytes were most abundant in V1 (59%) and EC (21%), respectively, and their transcriptomic profiles were anticorrelated. Reactive astrocytes were enriched in cytoskeleton ( GFAP MAP2, MAP7, MAPB1, MAPT ), extracellular matrix ( CD44, LAMA1, TNC, VCAN ), chaperones ( CRYAB, HSPB1, HSPB8 ), and oxidative stress/antioxidant ( MAOB, MT1X, MT2A, SOD2 ) genes, whereas homeostatic subclusters in trophic factor ( EGFR, PTN ) and glutamate metabolism ( GLUL, GRIA2, GRM3, SLC1A2 ) genes. The proportion of intermediate astrocyte subclusters was lowest in EC (25%) and highest in BA46 (41%), and their transcriptome correlated weakly with that of homeostatic and reactive astrocytes, representing an apparent gradient between homeostatic and reactive. Notably, these intermediate subclusters demonstrated the most heterogeneity among brain regions. Conclusion: Our astrocyte snRNA‐seq dataset encompassing five regions of control and AD brains revealed homeostatic, reactive, and previously uncharacterized intermediate astrocytic states with distinct transcriptomic profiles for each brain region, suggesting complex, region‐specific responses to AD pathology.